Environmental Policy and the Institutional System of Environment Protection in the Carpathian Basin - Duray, Balázs; Mezei, István; Nagy, Imre; PÁNOVICS, Attila (Discussion Papers, 2012)
The objective of the study is to define, through a complex survey of the environmental policy and institutional system, the impacts of the environmental policies in the Carpathian Basin and to compare and typify the attempts aiming at the implementation of environmental policies. A theoretical and practical significance of the research is that it may reveal the relations system in both the horizontal (among the regions or countries) and vertical sense (sectoral systems: environment protection, nature protection and water management). The findings of the research would contribute to the implementation of a single environmental policy, as well as the management and institutional system of environment and nature protection in the changing European Union.